Martensitic Transformation and Mechanical Properties of Fe-added Au-Cu-Al Shape Memory Alloy with Various Heat Treatment Conditions. Issue 1760 (19th December 2014) - Umise, Akira; Tahara, Masaki; Goto, Kenji; Inamura, Tomonari; Hosoda, Hideki
ABSTRACT: In order to improve shape memory properties of Au-Cu-Al based shape memory alloys, the possibility to utilize thermo-mechanical treatment was investigated in this study, and effects of heat-treatment temperature on microstructure, martensitic transformation and mechanical properties of cold-rolled Au-30Cu-18Al-2Fe (AuCuAlFe) alloy were clarified by X-ray diffraction analysis (XRD, differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and tensile tests at room temperature (RT). Here, Fe addition to AuCuAl improves ductility. Cold rolling with the thickness reduction of 30% was successfully carried out in AuCuAlFe at RT. An exothermic heat was observed in DSC at temperature from 402K, suggesting that recovery started at 402K. Besides, the transformation temperature hysteresis increased by the cold-rolling. The alloy was completely recrystallized after the heat treatment at 573K for 3.6ks. Tensile tests revealed that the yield stress was raised by cold rolling and largely by the subsequent heat treatment at 433K, which corresponded to the recovery start temperature by DSC. The yield stress decreased with increasing heat treatment temperature over 453K, probably due to recrystallization. AuCuAlFe cold-rolled and subsequent heat-treated at 573K exhibited the lowest yield stress as well as stress-plateau region, indicating that the thermo-mechanical treatment is effective to improve shape memory properties of Au-Cu-Al based alloys.